A transpersonal critique of behaviorism - Thornton, Edward E. (1982)
Behavioral psychology has been neglected by pastoral psychologists to the hurt of both. An examination of the principles of behaviorism and some of the data on the behavioral treatment of the neuroses is followed by an analysis of B.F. Skinner's philosophy of science. A critique is developed from the perspective of transpersonal psychology, concluding with a possible reconciliation of the opposites of behavioral and transpersonal ways of knowing.
Keywords: Behavioral Psychology; Behavioral Treatment; Pastoral Psychologist; Transpersonal Psychology